Specific Learning Disabilities - Argiropoulos, Dimitris (Psychological Counseling and Psychotherapy, 2019)
This article reports the specific disorders and difficulties in school learning settings and its frequent and relevant problems, as outlined in psychological literature and pedagogical sciences. These definitions are recognized and fully contemplated by the Law in several European countries, including Italy, and treatment, educational and relational guidelines are proposed, to be considered in a logic of protection and promotion of the child’s well-being (as a children or teen) with its specific learning disability. This document contains a first approach to the subject, aimed to inform and guide for the identification and distinction of this pathologies, which can coexist, and to limit their negative effects, which could compromise the child’s growth and development, especially if addressed early. Specific learning disabilities are related to reading, writing and mathematical calculation; it is important that in a school context the operators are (in) formed, in order to face and guarantee every day the realization of student’s learning and educational work in general.